Sistem Informasi Pemesanan Laundry Berbasis Android Di Kota Palembang - Evan Susanto; Tri Hartati Utami; Dedy Hermanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
Laundry is a facility where clothes are washed and dried. Laundry usually uses an automatic washing machine called laundromat or a general trademark. With the development of fashion models and various other types of equipment make the laundry service business increased, but the increasing number of laundry services business also means increased competition. This makes laundry business owners both those who have long been operating or those who are just starting to have trouble finding prospective customers and also promoting their business, on the other hand for customers or prospective customers also have difficulty finding laundry services that have quality services and desired criteria. Therefore, the author intends to make an Android-Based Laundry Ordering Information System in Palembang City. The process of developing this information system uses the Rational Unified Process (RUP) method. The author also use PIECES and Usecase Diagram in the analysis phase. At the design stage using Class Diagrams. Application development using the Java programming language and MYSQL as database. This information system is expected to be able to help laundry service business owners in overcoming problems that often occur in running their business processes, and also to facilitate prospective customers in looking for laundry services they want.